Interdecadal Shift in Dipole Pattern Precipitation Trends Over the Tibetan Plateau: Roles of Local Vortices - Li, Lun; Zhang, Renhe (Geophysical research letters, 2023)
Trends of precipitation over the Tibetan Plateau (TP) are characterized by a north‐south dipole pattern, and the role of local mesoscale systems, TP vortices (TPVs), remains ambiguous. This work reports that the north‐south dipole pattern trends in the TPVs‐associated precipitation have experienced an interdecadal shift in the last two decades, that is, increases in northern TP and decreases in southern TP first and then varies opposite trends, which greatly contributes to the similar interdecadal shift in TP precipitation trends. Furthermore, the causes of changes in TPV frequency are explored from the perspective of lower troposphere conditions. We find that the lower‐level winds, that is, zonal winds over the TP and meridional winds across the northwestern TP boundary, are responsible for the regionally different variations in TPV frequency. The variations in Indian Ocean Dipole are suggested to contribute to the changes in lower‐level winds over the TP. Plain Language Summary Precipitation over the Tibetan Plateau (TP) significantly affect local and downstream water resources, which generally presents dipole pattern trends, that is, opposite precipitation trends in the northern TP (NTP) and in southern TP (STP). However, the physical processes of the variations in TP precipitation, especially the roles of local mesoscale systems, TP vortices (TPVs), are not yet clear. In this work, dipole pattern variations are found in TPVs‐associated precipitation, which experienced an interdecadal shift in the last two decades, that is, increases in NTP and decreases in STP first and then varies opposite trends. The interdecadal shift in the TPVs‐associated precipitation trends greatly contributes to the interdecadal shift in the TP precipitation trends. Furthermore, the causes of variations in TPV frequency are explored, and find that the changes in zonal winds over the TP and meridional winds across the northwestern TP boundary are closely related to the regionally different variations in TPV frequency. Subsequently, the changes in the sea surface temperature of India Ocean are demonstrated to be responsible for the wind variations. Key Points North‐south dipole pattern precipitation trends over the Tibetan Plateau (TP) have experienced an interdecadal shift in the last two decades Changes in TP vortices (TPVs) contribute to the interdecadal shift in the TP precipitation trend pattern Sea surface temperature of India Ocean is responsible for variations in lower‐level winds, prompting changes in TPVs